Hisab Method in Order to Resolve Differences in Arafah Fasting Between Indonesia With Saudi Arabia: A Study of Professor Syamsul Anwar's Thoughts - Ahmad Yunan Siregar (AT-TAFAHUM: Journal of Law, 2017)
According to Professor Syamsul Anwar, this rukyat method has various obstacles, including among the natural obstacles is the limited range of rukyat, especially at the beginning of the month, which is visible from the surface of the earth. Therefore, it will differ between countries that have seen it and areas that have not. In other words, rukyat is a universal tool but applies temporally and locally. Therefore, according to him, the method that can unify the beginning of the lunar month is the hisab method because this method is more accurate reliable for now. Which the problems in this research are: (1) how does Professor Syamsul Anwar view Rukyatul Hilal in relation to the beginning of the lunar month, (2) how does Professor Syamsul Anwar think about hisab and (3) what efforts can be made to unify religious moments such as Eid al-Fitr, Eid al-Adha including the differences in the implementation of the Arafah fast between Indonesia and Saudi Arabia. The results of the research show that the rukyat method according to Professor Syamsul Anwar causes many obstacles, because the range of rukyat is limited in its appearance on the surface of the earth, it is possible that the hilal is visible in Saudi Arabia, but not in Indonesia. The hilal may be visible in America but not in Saudi Arabia. Because of the differences in rukyat in various places, the beginning of the month also falls differently, this is different from hisab, because hisab does not experience obstacles with natural factors, because it calculates the actual movement of the moon, so the hisab method can determine the beginning of the month simultaneously throughout the world.